088 The walton seizure pathway – experience to date and outcomes. Issue 12 (14th November 2019) - Fletcher, Nicholas; Marson, Anthony; Riley, Julie; Wilson, Martin; Nicolson, Andrew
Abstract : We designed a seizure management pathway for A&E and acute medical units of Walton Neuro Network hospitals. This was in response to the results of the National Audit of Seizures in Hospitals (NASH) revealing considerable variation in management and referral of patients after seizures. It was established with a varying degree of success in seven acute trusts. Its aims were: 1. clear admission and discharge criteria; 2. guidance on management of patients requiring admission, status epilepticus and obtaining inpatient advice or consultation if needed; 3. a simple pathway for all seizure patients to be referred quickly to WCFT after discharge from A&E or an acute medical ward; 4. to reduce repeat A&E attendances and re-admissions; 5. clear patient information for all patients discharged from A&E or inpatient care after seizures. The outcome was reviewed for 2016–2018. More seizure patients were referred (+23%); the proportion of patients seen in a neurology clinic after a seizure related admission increased from 34% to 42% and the proportion of seizure patients admitted to local hospitals who were not under neurology follow up fell from 58% to 48%. However, the referral rate after admission of new (or not under review) seizure patients remains too low at 21%. There has been no effect yet on re-admission or A&E re-attendance rates of patients after seizure admissions.